A new organic reference material, l‐glutamic acid, USGS41a, for δ13C and δ15N measurements − a replacement for USGS41. (1st March 2016) - Qi, Haiping; Coplen, Tyler B.; Mroczkowski, Stanley J.; Brand, Willi A.; Brandes, Lauren; Geilmann, Heike; Schimmelmann, Arndt
Abstract : Rationale: The widely usedl ‐glutamic acid isotopic reference material USGS41, enriched in both 13 C and 15 N, is nearly exhausted. A new material, USGS41a, has been prepared as a replacement for USGS41. Methods: USGS41a was prepared by dissolving analytical gradel ‐glutamic acid enriched in 13 C and 15 N together withl ‐glutamic acid of normal isotopic composition. The δ 13 C and δ 15 N values of USGS41a were directly or indirectly normalized with the international reference materials NBS 19 calcium carbonate ( δ 13 CVPDB = +1.95 mUr, where milliurey = 0.001 = 1 ‰), LSVEC lithium carbonate ( δ 13 CVPDB = −46.6 mUr), and IAEA‐N‐1 ammonium sulfate ( δ 15 NAir = +0.43 mUr) and USGS32 potassium nitrate ( δ 15 N = +180 mUr exactly) by on‐line combustion, continuous‐flow isotope‐ratio mass spectrometry, and off‐line dual‐inlet isotope‐ratio mass spectrometry. Results: USGS41a is isotopically homogeneous; the reproducibility of δ 13 C and δ 15 N is better than 0.07 mUr and 0.09 mUr, respectively, in 200‐μg amounts. It has a δ 13 C value of +36.55 mUr relative to VPDB and a δ 15 N value of +47.55 mUr relative to N2 in air. USGS41 was found to be hydroscopic, probably due to the presence of pyroglutamic acid. Experimental results indicate that the chemical purity of USGS41a is substantially better than that of USGS41. Conclusions: The new isotopic reference material USGS41a can be used with USGS40 (having a δ 13 CVPDB value of −26.39 mUr and a δ 15 NAir value of −4.52 mUr) for (i) analyzing local laboratory isotopic reference materials, and (ii) quantifying drift with time, mass‐dependent isotopic fractionation, and isotope‐ratio‐scale contraction for isotopic analysis of biological and organic materials. Published in 2016. This article is a U.S. Government work and is in the public domain in the USA.